2019
DOI: 10.1080/13696998.2019.1592180
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilization by patients with treatment-refractory myasthenia gravis in England

Abstract: Aims: To examine healthcare resource utilization associated with refractory myasthenia gravis (MG) in England. Materials and methods: This was a retrospective cohort study of linked data from the Clinical Practice Research Datalink and the Hospital Episode Statistics database collected between 1997 and 2016. Included patients were !18 years of age at the index MG diagnosis. Patients with refractory MG were identified using an algorithm based on treatments received. Healthcare resource utilization since the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…The results of the current study are consistent with previous publications describing increased HRU in people with refractory versus nonrefractory MG. 10 , 24 , 25 The current study extended the duration of follow-up by at least 1 year compared with the study by Engel-Nitz et al 10 and suggested longer-lasting effects of experiencing refractory disease.…”
Section: Discussionsupporting
confidence: 49%
“…The results of the current study are consistent with previous publications describing increased HRU in people with refractory versus nonrefractory MG. 10 , 24 , 25 The current study extended the duration of follow-up by at least 1 year compared with the study by Engel-Nitz et al 10 and suggested longer-lasting effects of experiencing refractory disease.…”
Section: Discussionsupporting
confidence: 49%
“…J Med Econ. 2019;22(7):691-697 Dear Editor, We would like to thank the authors of this letter for their comments on our study published in 2019 1 . The authors made two points in their commentary based on our paper.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Firstly, the refractory MG patients and non-MG controls were compared for rates of GP visits, hospitalisations, emergency and outpatient visits. In this analysis the differences in the length of follow-up period was controlled for either (1) through presenting the results per person-years of follow up (rates) or (2) through including follow-up as an offset variable in the logistic or binomial models. In the context of a long-term chronic disease such as MG, there is a scientific interest at describing the healthcare resource use over long period of times, and we had no reason to think that the rates of HCRU would vary over the person-years of follow-up.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Details of the study design were described previously [19]. Brie y, the study included patients in England with a diagnosis of MG who were ≥18 years of age at the date of rst MG diagnosis (index date) and who had linked data in CPRD and HES.…”
Section: Study Design and Conductmentioning
confidence: 99%
“…We recently described healthcare resource utilization by patients with refractory and non-refractory MG in England using data from the Clinical Practice Research Datalink (CPRD) and Hospital Episode Statistics (HES) databases collected from 1997 to 2016 [19]. As reported in the US and Japan using claims data [14,16], the rates of general practitioner visits, visits to other healthcare professionals, outpatient visits, and inpatient hospitalization were signi cantly higher for patients with refractory MG than for patients with non-refractory MG.…”
Section: Introductionmentioning
confidence: 99%